Konstruksi Musikal Sekar Anyar dalam Tembang Sunda Cianjuran: Analisis Struktur Dongkari dan Formula Ornamen pada Lagu “Wegah”-“Sajeroning Sindang” - Dika Dzikriawan; Wiwik Sushartami; Aton Rustandi Mulyana (Universitas Gadjah Mada, 2021)
ABSTRACTSekar anyar is tembang sunda cianjuran innovation who created by Ubun Kubarsah. The term of serkar anyar in tembang sunda cianjuran first appeared in the XIX Pasanggiri Tembang sunda cianjuran (PTSC) Daya Mahasiswa Sunda (DAMAS) that goes on Graha Sanusi Universitas Padjadjaran (UNPAD) Bandung in December 2009. During this time, sekar anyar in tembang sunda cianjuran is still a debate among the tembang sunda cianjuran community. The discourse that appears in the sekar anyar is basically debating about the terminology itself, the problem of characteristics (in this case, the issue of musical and non-musical), the issue of character assassination, to the issue of whether sekar anyar is fit to be included in the category of the tembang sunda cianjuran genre. The following resarch aims to explain how the musical construction of sekar anyar in the tembang sunda cianjuran from the perspective of using the dongkari structure and the formula ornamen in the song